From magnesite directly to lightweight closed-pore MgO ceramics: The role of Si and Si/SiC. Issue 22 (15th November 2021) - Ren, Xinming; Ma, Beiyue; Wang, Lulu; Liu, Guoqi; Yu, Jingkun
Abstract: Partial/full replacement of traditional dense refractory aggregates (for furnace lining) with lightweight aggregates is considered to be an effective and promising strategy for energy saving and emission reduction. In this work, lightweight magnesia refractory ceramics with tailored closed porosity were prepared by one-step sintering at 1600 °C from high-purity magnesite added with silicon kerf waste in different ratios, with the emphasis on the evolution of their phase compositions, micromorphologies, and various properties. With the addition of additives, Mg2– x Fe x SiO4 solid solution was formed at the grain boundaries of the MgO matrix, and then the volumetric expansion effect (interfacial reaction) and activated sintering effect (vacancy defect) promote the decrease of apparent porosity and the increase of closed porosity, respectively. Consequently, MgO ceramics with apparent/closed porosity of 0.6%/6.5%, bulk density of 3.25 g cm −3, and lightweight index of 7.8% were successfully prepared, suitable for the working lining of metallurgical furnaces.